Airway remodeling blockade with an orally active geranyl acetophenone - Lee, Yu Zhao (2017)
n the last few decades, structural changes of airways in asthma has gained huge attention from both clinicians and scientists as current therapeutic approaches are inadequate in attenuating airway remodeling, especially in severe asthma patients. Airway remodeling includes subepithelial fibrosis, thickening of basement membrane, hyperplasia and metaplasia of epithelialand goblet cells, mucosal gland enlargement and increase in smooth musclemass with loss of lung function. Current asthma treatment with corticosteroids that suppress lung inflammation and bronchodilators which ease breathing difficulties have limited effect on airway remodeling. In addition, there are 10% of patients do not respond to treatment. Moreover, noncompliance in asthma patients to inhaler devices is also a major problem. Newintervention is clearly needed to address these issues. 2,4,6-trihydroxy-3-geranyl acetophenone (tHGA) is a synthetic compound naturally found in Melicope ptelefolia. Intraperitoneal administration of tHGA is able to reduce lung inflammation in a murine model of acute asthma. In this study, the efficacy of orally administered tHGA upon airway remodeling in a murine model of chronic asthma was evaluated. The mode of action was assessed via model of eosinophil-induced epithelial-mesenchymal transition. A standard 6 week ovalbumin-challenged BALB/c mice model of chronic asthma was used. Oral tHGA treatment was found to attenuate airway hyperresponsiveness and remodeling in a dose-dependent fashion. tHGA’s dose of 80 mg/kg per os was found to be most effective while 20 mg/kg did not exert any effect. The deposition of extracellular matrix proteins (collagen I, fibronectin and tenascin C) and hyperplasia of myofibroblasts and smooth muscle cells was also inhibited by tHGA.tHGA’s effect on airway remodeling could beattributed to the reduction of inflammatory cell infiltration and decreased expression of cytokines associated with airway remodeling like interleukin (IL)-4, IL-13 and transforming growth factor (TGF)-β. Epithelial-mesenchymal transition (EMT) is currently recognized as the main cellular event that contributes to airway remodeling. The effect of synthetic 2,4,6-trihydroxy-3-geranyl acetophenone (tHGA) upon eosinophil-induced epithelial-mesenchymal transition in a cellular model was assessed. The human eosinophil cell line EoL-1 was used to induce EMT in BEAS-2B human bronchial epithelial cells. The induction of EMT was dose-dependently suppressed following tHGA treatment in which the epithelial morphology and E-cadherin expression were not altered. Protein and mRNA expression of vimentin, collagen I and fibronectin in eosinophil-induced epithelial cells were also significantly suppressed by tHGA treatment. The protein and gene expression of TGF-βwere found to be significantly inhibited by 30μM tHGA. However, tHGA was incapable of impeding TGF-β-induced EMT in BEAS-2B cells. Following pathway analysis, tHGA was found to suppress eosinophil-induced activator protein-1 (AP-1)-mediated TGF-β production in bronchial epithelial cells bytargeting c-Jun N-terminal kinase (JNK) and phosphoinositide 3-kinase (PI3K) signaling pathways. In conclusion, tHGA’s effective inhibition on TGF-βproduction may largely contributed to its capacity in ameliorate airway remodeling. Our findings potentiate the possibility of tHGA’s development as a new non-steroidal oral lead for the management of asthma.